1988
DOI: 10.1590/s0037-86821988000300008
|View full text |Cite
|
Sign up to set email alerts
|

Diagnóstico sorológico da estrongiloidíase humana através do método imunoenzimático

Abstract: O presente trabalho demonstra a eficácia do método imunoenzimático utilizando antígeno solúvel de larvas de Strongyloides stercoralis no diagnóstico da estrongiloidíase humana. Foram avaliados 27 pacientes com as diversas formas clínicas da parasitose, sendo demonstrados títulos significativos em 25 (92%) dos casos. Em 17 controles, com ou sem outrasparasítoses intestinais, títulos significativos estavam presentes em 3 (18%). A sensibilidade do teste foi de 92% e a especificidade de 82%. São também relatados 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…14,15,17,[28][29][30] In a previous study done in Brazil in a region endemic for strongyloidiasis, the sensitivity was 92% in the general population of immunocompetent individuals. 27 Our lower sensitivity may be explained by the reduction of antibody production because of the immunosuppression. Indeed, the optical density values of the sera from the immunocompromised patients were significantly lower than the values of the control sera.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…14,15,17,[28][29][30] In a previous study done in Brazil in a region endemic for strongyloidiasis, the sensitivity was 92% in the general population of immunocompetent individuals. 27 Our lower sensitivity may be explained by the reduction of antibody production because of the immunosuppression. Indeed, the optical density values of the sera from the immunocompromised patients were significantly lower than the values of the control sera.…”
Section: Discussionmentioning
confidence: 90%
“…20 The specificity of the test observed in the present study was similar to the results reported in immunocompetent people, which ranged from 82% to 100%. 14,15,18,27,30,31 Although sensitivity and specificity are intrinsic properties of any given test, the positive and negative predictive values are the most useful information for the user of the test because they represent the rate of true positive and true negative cases, with the results varying depending on the prevalence of the infection in the study area. In our study, the positive predictive value of the ELISA was very low, reflecting a very high rate of false-positive results (half of the positive results).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies support the view that detection of parasite-specific antibodies may be a useful complement to the traditional parasitological diagnosis of strongyloidiasis using the indirect immunofluorescence antibody test (IFAT) 4,12 and enzyme-linked immunosorbent assay (ELISA) 3,13,22 .…”
mentioning
confidence: 97%